Baseline Characteristics of Patients and the Effect of Fixed-Dose Combination Chemotherapy on Sputum Conversion Time in Active Pulmonary Tuberculosis: A Preliminary Study in Kandy District, Sri Lanka - Jayawardena, KAS; Samarathunga, M (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
Main Objective: To evaluate the effect of Fixed-Dose Combination (FDC) drugs on sputum conversion time in active tuberculosis. Method: A prospective study of 58 active pulmonary tuberculosis patients in Kandy District Sri Lanka. Results: The mean sputum conversion time was 3.836 weeks (SD 2.599) and the median was 4.00 weeks. The sputum conversion rate at the end of 8 weeks was 96.36%. Initial bacillary load indicated by sputum smear grading was highly correlated with sputum conversion time (r = 0.531 P = 0.000). Gender was associated with sputum conversion time. Women had significantly shorter sputum conversion time. (T value =2.23, P = 0.03, Df = 48). Heavy smoking was associated with delayed sputum conversion in male patients (p = 0.01). Conclusion: Use of FDC in active pulmonary tuberculosis yields high sputum conversion rate with a mean sputum conversion time of 3.4 weeks. Faster sputum conversion among women may be attributed to their stronger genetic constitution and healthy lifestyles. Heavy smoking is associated with delayed sputum conversion. Key words: FDC Drugs; sputum conversion time; pulmonary tuberculosis; Sri Lanka DOI: 10.3126/saarctb.v5i1.3076 SAARC J. Tuber. Lung Dis. HIV/AIDS 2008 Vol.5(1) 1-6